A practical approach to assessing and managing sexual dysfunction in multiple sclerosis. Issue 2 (21st November 2019) - Li, Vivien; Haslam, Collette; Pakzad, Mahreen; Brownlee, Wallace J; Panicker, Jalesh N
Abstract : Sexual dysfunction is common in both men and women with multiple sclerosis but is often under-reported and undertreated. Neurologists report that a major barrier to discussing sexual dysfunction with patients is their lack of knowledge. Here we review the common presentations of sexual dysfunction, discuss its causes in people with multiple sclerosis, and provide a practical approach for neurologists to assess and manage these problems.